2020
DOI: 10.1016/j.atherosclerosis.2020.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid atg5 deletion impairs n-3 PUFA-mediated atheroprotection

Abstract: Background and aims: Dietary long-chain (≥ 20 carbons) n-3 polyunsaturated fatty acids (PUFAs) reduce atherosclerosis and enhance macrophage autophagy activation. How macrophage autophagy impacts atherosclerotic progression, particularly when comparing dietary n-3 PUFA supplementation vs. saturated fat feeding, is unknown. Methods:We generated myeloid-specific autophagy-deficient and control mice in the Ldlr −/− background by transplanting bone marrow from myeloid-specific autophagy-related (atg) 5 knockout mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…Finally, the authors demonstrated that the endothelial knockdown of Atg5 or the pharmacological inhibition of autophagy resulted in a similar in vivo alteration of hemostasis [ 95 ] Accordingly, Atg7 deletion is associated with a reduction in arterial thrombosis in a murine model of atherothrombosis [ 96 ]. Moreover, Atg5 interaction is necessary to promote n-3 polyunsaturated fatty acid (n3 PUFA)-induced atheroprotection [ 97 ]. Recently, autophagy has been proven to be an important tool in the differentiation of stem cells into endothelial lineage by promoting angiogenesis through the release of proangiogenic factors in a paracrine manner [ 98 ].…”
Section: Autophagy In Endothelial Cell Biologymentioning
confidence: 99%
“…Finally, the authors demonstrated that the endothelial knockdown of Atg5 or the pharmacological inhibition of autophagy resulted in a similar in vivo alteration of hemostasis [ 95 ] Accordingly, Atg7 deletion is associated with a reduction in arterial thrombosis in a murine model of atherothrombosis [ 96 ]. Moreover, Atg5 interaction is necessary to promote n-3 polyunsaturated fatty acid (n3 PUFA)-induced atheroprotection [ 97 ]. Recently, autophagy has been proven to be an important tool in the differentiation of stem cells into endothelial lineage by promoting angiogenesis through the release of proangiogenic factors in a paracrine manner [ 98 ].…”
Section: Autophagy In Endothelial Cell Biologymentioning
confidence: 99%
“…Elevated availability of saturated FAs in the HSCs dampens the activity of autophagy related 5 (Atg5), a key protein involved in the extension of the phagophoric membrane in autophagic vesicles, and this results into reduced cellular mitochondrial cellular mass of hematopoietic cells committed to become lymphocytes, in favor of a preferential expansion of the myeloid compartment. Also, Atg5 repression in myeloid lineage aggravates atherosclerosis and negatively impact on the inflammatory composition of atherosclerotic lesions in mice fed on diet enriched in polyunsaturated fats (PUFAs) [ 52 ], lipid dietary sources that favors the activity of macrophage autophagy [ 53 ]. Accordingly, myeloid skewing of hematopoietic cells appears proportional to the quantity of white adipose tissue volume in the mid-shaft of the bones [ 54 , 55 ].…”
Section: Cellular Energetic Circuits Involved In Hematopoietic Cell Cmentioning
confidence: 99%
“…Total RNA in the liver, adipose tissue, peritoneal macrophages, or BMDMs was extracted using Trizol (Invitrogen). cDNA preparation and real-time PCR were conducted as described previously (25,61).…”
Section: Cytokine Quantificationmentioning
confidence: 99%
“…BMT: BMT was performed as described before (61). Briefly, male Ldlr -/recipient mice at 7 wks of age received a sublethal dose of radiation (900 rads) 4 h prior to bone marrow injection.…”
Section: Animals Bone Marrow Transplantation (Bmt) and Diet Feedingmentioning
confidence: 99%
See 1 more Smart Citation